Implementasi Pelaksanaan Pembelajaran Daring di Masa New Normal Pada Mata Pelajaran Pendidikan Agama Islam di SMA Negeri Ploso - Lilawati, Emi; Dheafana, Nabilla (JoEMS (Journal of Education and Management Studies), 2023)
The Covid-19 pandemic is a real problem throughout the world, where with the outbreak of the Covid pandemic cases, there are many impacts in various sectors, especially in the education sector, economy, commerce and many more. The most disturbing thing in the implications of the covid 19 pandemic is in the education sector. Indonesia as a country that is late in responding to globalization, of course, with the Covid-19 pandemic, is intended to immediately adapt, including in the world of education. Learning in schools, which was originally carried out offline or face-to-face, with the pandemic, is required to be able to collaborate with technology such as applying online learning even though we realize that learning is very inefficient and tends to improve and cut students' understanding. The impact that the Covid-19 pandemic was born during the New Normal era is in resources such as very slow and or unreliable and unstable internet connections, noisy online classrooms and lack of privacy during online classes simultaneously, lack of a licensed/registered Learning Management System (LMS) to continuously hold online classes and the lack of computers and internet connections for some educators. Educators are physically prepared for New Normal teaching, but educators are not emotionally prepared, therefore educators prefer to teach in the classroom rather than in a virtual classroom. The impact on educator adjustment is in terms of the student environment, curriculum, teaching strategies, and the use of technology. The age, gender, type of school and level of students taught by educators are factors that influence student teaching in the New Normal era.